Modeling swelling behavior of hydrogels in aqueous organic solvents. (12th October 2021) - Islam, Md Rashedul; Tanveer, Sheik; Chen, Chau-Chyun
Graphical abstract: Highlights: Solvent – hydrogel interactions are the dominant driving force for hydrogel swelling. Polymer NRTL activity coefficient model accounts for the solvent – hydrogel interactions. The model correlates data for both swelling and equilibrium phase compositions. Hydrogels deswell if the hydrogel – solvent mixture forms an ideal solution. Abstract: Hydrogel, a three-dimensional elastic structure of cross-linked polymer chains, swells or deswells when immersed in aqueous organic solutions. The swelling of hydrogels depends on temperature, solvent composition, and hydrogel structure as the thermodynamic driving forces for hydrogel swelling are due to solvent – hydrogel interactions and expansion of elastic network. In this work, polymer Nonrandom Two-Liquid activity coefficient model is used to account for the solvent – hydrogel interactions and a semi-empirical expression for rubber elasticity is used to describe the expansion of elastic network. The model successfully correlates data for both swelling and equilibrium phase compositions for n -isopropyl acrylamide hydrogels in water – ethanol, water – acetone, water – n -butanol, and water – methyl isobutyl ketone mixed solvents.